Transmission Dynamics of COVID-19 in Nepal - Adhikari, Khagendra; Shrestha, Dhan Bahadur; Gautam, Ramesh; Pokharel, Anjana (Humanities and Social Sciences Journal, 2021)
In this paper, we use the basic SEIR model to study the transmission dynamics of COVID-19 in Nepal. Fitting the model with the data of Nepal, we estimated 26% of Seroprevalence from 13 March, 2021 and the level of control strategies to reduce COVID-19 cases in Nepal. The value of β is approximated 0.0536 for the study period. Reduction of β by 25%, 50%, 75%, reduces reported cumulative cases by the end of 13th March, 2021 by 34.5%, 55.6% and 68.7% respectively.